NMDAR in bladder smooth muscle is not a pharmacotherapy target for overactive bladder in mice - Xiang Xie; Chuang Luo; Jia Yu Liang; Run Huang; Jia Li Yang; Linlong Li; YangYang Li; Hongming Xing; Huan Chen (PeerJ, 2021)
Overactive bladder (OAB) is a common condition that affects a significant patient population. The N-methyl-D-aspartate receptor (NMDAR) has a role in developing bladder overactivity, pharmacological inhibition of which inhibits bladder overactivity. The common pathogenesis of OAB involves bladder smooth muscle (BSM) overactivity. In this study, a smooth muscle–specific NMDAR knockout (SMNRKO) mouse model was generated. The bladders from SMNRKO mice displayed normal size and weight with an intact bladder wall and well-arranged BSM bundles. Besides, SMNRKO mice had normal voiding patterns and urodynamics and BSM contractility, indicating that NMDAR in BSM was not essential for normal physiological bladder morphology and function. Unexpectedly, cyclophosphamide (CYP)-treated SMNRKO and wild-type (WT) mice had similar pathological changes in the bladder. Furthermore, SMNRKO mice displayed similar altered voiding patterns and urodynamic abnormalities and impaired BSM contractility compared with WT mice after CYP treatment. MK801 partially reversed the pathological bladder morphology and improved bladder dysfunction induced by CYP, but did not cause apparent differences between WT mice and SMNRKO mice, suggesting that NMDAR in BSM was not involved in pathological bladder morphology and function. Moreover, the direct instillation of NMDAR agonists or antagonists into the CYP-induced OAB did not affect bladder urodynamic function, indicating that NMDAR in BSM was not the pharmacotherapy target of MK801 for CYP-induced cystitis. The findings indicated that NMDAR in BSM was not essential for normal physiological or pathological bladder morphology and function, and MK801 improving pathological bladder function was not mediated by an action on NMDAR in BSM.